Interactions Between Nutrition Professionals and Industry: A Scoping Review - Virginie Hamel; Marita Hennessy; Mélissa Mialon; Jean-Claude Moubarac (Kerman University of Medical Sciences, 2023)
Background  In recent years, interactions between nutrition professionals (NPs) and the food industry, such as sponsorship arrangements, have raised concerns, particularly as these may negatively impact the trustworthiness and credibility of the nutrition profession. This study aimed to map the literature and identify knowledge gaps regarding interactions between NPs and industry. We sought to examine the nature of such interactions and NPs perspectives about these, as well as the risks and solutions.Methods  We conducted a scoping review according to a pre-registered protocol, searching eight electronic databases and grey literature sources in March 2021 to identify documents for inclusion. Two independent reviewers screened citations for inclusion and conducted data extraction. Quantitative and qualitative syntheses were conducted.Results  We identified 115 documents for analysis, published between 1980 to 2021, with a majority from the United States (n = 59, 51%). Only 32% (n = 37) were empirical studies. The food industry was the most frequent industry type discussed (n = 91, 79%). We identified 32 types of interactions between NPs and industry, such as continuing education provided by industry and sponsorship of professional bodies and health and nutrition organizations. The financial survival of nutrition organizations and continuing education access for NPs were the most frequently cited advantages of industry-NPs interactions. On the other hand, undermining public trust, NPs credibility and public health nutrition recommendations were pointed out as risks of these interactions. Following a code of ethics, policies, or guidelines was the most frequently proposed solution for managing these interactions.Conclusion  Despite the increasing attention given to this issue, few empirical papers have been published to date. There is a need for more research to better and systematically document industry interactions with NPs and the impacts associated with these, as well as more research on effective management strategies.